Improvement of Method for Distance Detection of Damaged Section at One-Phase Ground Fault in Urban Distributive Networks - M. D. Diachenko; A. S. Mironov; V. V. Bourlaka; S. K. Podnebennaya (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2010)
Methodology for distance detection of ground fault point in the networks with an insulated neutral for cable lines with distributed loads and parameters of emergency mode have been developed in the paper. The paper proposes an algorithm of automatic one-phase ground fault in the urban cable distributive networks with indication of damage point. The possibility of centralized damage detection is considered in the paper.